Swim cast versus traditional cast in pediatric distal radius fractures: A prospective randomized controlled trial. (March 2013) - Derksen, Robert Jan; Commandeur, Joris P.; Deij, Ronald; Breederveld, Roelf S.
Abstract: Purpose: Non-displaced distal radius fractures in children are traditionally treated in a forearm cast. However, a traditional cast does not tolerate getting wet, with skin lesions and bad smell as result. A Swim cast, which has the ability to dry quickly, is an airy cast that is applied using the MOKcast technique. We hypothesize that Swim casts contribute to higher patient satisfaction scores than traditional casts, without any adverse effects on fracture healing or skin condition. Methods: A prospective, randomized, single-center, blinded study was conducted to compare traditional and Swim cast treatment in children aged 5–15 years with greenstick or torus fractures of the distal radius. Primary endpoint was the patient and parent satisfaction, as determined by a questionnaire. Secondary endpoints were radiographic and clinical bone healing and cast-related skin conditions. Results: A total of 68 patients, divided into two treatment groups (traditional case and Swim cast; n = 34 per group). Baseline characteristics were similar between the groups. The overall satisfaction score (0–10) reported by the patients was 8.6 in the Swim cast group versus 7.5 in the traditional cast group ( p < 0.002); the overall satisfaction score reported by the parents was 8.3 and 7.7, respectively ( p < 0.02). There was no difference in radiographic or clinical healing between groups, and skin conditions also did not differ significantly between groups. Conclusion: In our patient group, treatment of non-displaced, pediatric, distal radius fractures by Swim cast yielded better patient satisfaction results compared to treatment with the traditional, cotton-lined cast, without adverse effects on fracture healing or skin condition.